2022
DOI: 10.1109/lra.2022.3148982
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Functions for Simultaneous Attitude and Image Estimation With Event Cameras at High Angular Rates

Abstract: For fast-moving event cameras, projection of events onto the image frame exhibits smearing of events analogous to high motion blur. For camera attitude estimation, this presents a causality dilemma where motion prior is required to unsmear events, but an image prior is required to estimate motion. This dilemma is typically circumvented by including an IMU to provide motion priors. However, IMUs limited dynamic range of ±2000 • /s are shown to be insufficient for high angular rate rotorcrafts. Contrast Maximiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Each IWE pixel sums the values of the warped events that fall within it: if polarity is used or if polarity is not used. The Dirac delta is in practice replaced by a smooth approximation [ 33 ], such as a Gaussian, with pixel. A popular objective function is the visual contrast of the IWE ( 3 ), given by the variance with mean and image domain .…”
Section: Methodsmentioning
confidence: 99%
“…Each IWE pixel sums the values of the warped events that fall within it: if polarity is used or if polarity is not used. The Dirac delta is in practice replaced by a smooth approximation [ 33 ], such as a Gaussian, with pixel. A popular objective function is the visual contrast of the IWE ( 3 ), given by the variance with mean and image domain .…”
Section: Methodsmentioning
confidence: 99%
“…The delta δ in ( 5) is an idealized model amenable for integration. In practice it is replaced by a kernel, such as a Gaussian δ(x) ≈ N (x; 0, 2 Id), where ≈ 1 pixel and Id is the identity matrix [26], [36]. For speed-up, it is implemented using bilinear voting and Gaussian convolution [37].…”
Section: Generalization To Arbitrary Motions and Scenesmentioning
confidence: 99%
“…The spinning nature of the platform also helped in passively scanning and mapping the surrounding environment using Simultaneous Localization and Mapping (SLAM) in [12]. Similarly, in [13] and [14], the authors have shown applications for the monocopter for simultaneous image and onboard state estimation and LiDAR inertial odometry, respectively. On the other hand, a bicopter UAV uses two motors to generate collective lift force and torque in the roll axis using differential thrust.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, recent research has also demonstrated that the rotating wing platform has superior power efficiency compared to other platforms [22]. Monocopters can be employed for various applications where the spinning nature of the platform can be utilized, for example, passively scanning and mapping the surrounding environment as done in [12], [13]. However, even though the monocopter platform is based on a single wing, the physical footprint of the spinning drone is large enough to hinder its mobility.…”
Section: Introductionmentioning
confidence: 99%